Feasibility of the Prototype of Teaching Materials on the Topic of Classification of Living Things Based on the Advantage of Local Wetland - Fahmi Fahmi; Hery Fajeriadi; Yudha Irhasyuarna (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Competition in the field of education globally is increasingly competitive, but it has not been directly proportional to the development of education in several regions in Indonesia. Students still have difficulty in critical thinking, including the concept of classification of living things, because the teaching materials used are not fully related to the experience and environment of students. This study aims to develop teaching materials for the concept of classification of living things based on local potential. The development is carried out using Tessmer's formative model which includes five stages; 1) self-evaluation (self-evaluation); 2) expert opinion (expert review); 3) Individual trial (one to one); 4) small group trial; and 5) field test. The results showed that by developing a prototype of contextual teaching materials based on local advantages, it was able to increase students' interest, activity, and thinking skills which could be measured by increasing their learning outcomes.Abstrak Persaingan di bidang pendidikan secara global semakin kompetitif, namun belum berbanding lurus dengan perkembangan pendidikan di beberapa daerah di Indonesia. Peserta didik masih mengalami kesulitan dalam berpikir kritis, diantaranya pada konsep klasifikasi makhluk hidup, karena bahan ajar yang digunakan belum sepenuhnya berkaitan dengan pengalaman dan lingkungan hidup peserta didik. Penelitian ini bertujuan untuk mengambangan bahan ajar konsep klasifikasi makhluk hidup berbasis potensi lokal. Pengembangan dilakukan dengan menggunakan model formatif Tessmer yang meliputi lima tahapan; 1) evaluasi diri (self-evaluation); 2) pendapat pakar (expert review); 3) Uji coba perorangan (one to one); 4) uji coba kelompok kecil (small group); dan 5) uji lapangan (field test). Hasil penelitian menunjukkan bahwa dengan dilakukan pengembangan prototype bahan ajar kontekstual berbasis keunggulan lokal mampu meningkatkan minat, aktivitas, dan kemampuan berpikir siswa yang dapat diukur diantaranya dengan meningkatnya hasil belajarnya.